Reforming the Law of Nature the Secularization of Political Thought, 1532-1688 - Kennedy, Simon P. (Edinburgh studies in comparative political theory & intellectual history., 2022)
Uncovers the relationship between early modern natural law ideas and secular conceptions of politicsProvides a fresh interpretation of the historical relationship between early modern developments in natural law theories and important features of modern political thought, including secularization and liberalismOffers a fresh, interdisciplinary reading of early Reformed Protestant natural law jurisprudence and political thoughtReframes the relationship of the Reformed Protestant tradition to both medieval and Enlightenment political thought and jurisprudence in a way that has a lasting impact on scholarly discourse in law, intellectual history, theology, and political scienceReforming the Law of Nature is a stimulating study of the development of natural law ideas in the early modern period, uncovering their connection to conceptions of the origins of politics. It brings sixteenth and seventeenth century jurisprudence, theology and political philosophy into conversation with one another to uncover the ways in which developments in political thought affected the emergence of a secular understanding of political life.